The Impact of CEO Duality on the Relationship Between Board Characteristics and the Firm Performance of Companies Listed on The Stock Exchange of Thailand - Chankidkan, Pannapon; Sanpakdee, Pitan (Arts of Management Journal, 2025)
This research aimed to 1) study the impact of board characteristics on performance and 2) examine the influence of boards with combined executive positions on the relationship between board characteristics and the performance of listed companies on the Stock Exchange of Thailand. Quantitative research was conducted using secondary data from 482 listed companies, totaling 2,410 records, covering the period from 2020 to 2024, sourced from annual reports, financial statements (Form 56-1), and the SETSMART database. Descriptive and inferential statistics, including Pearson's product-moment correlation coefficient and multiple regression analysis, were employed. The results revealed that board size negatively impacts company performance, suggesting that companies with overly large boards may experience delays in decision-making and role ambiguity. The proportion of independent directors, the proportion of foreign directors, and the number of meetings were not statistically significant. Furthermore, companies perform better when they clearly separate the chairman and senior executive positions, as the combination of these roles negatively impacts their performance. Moreover, it was found that combined positions influence the relationship between board size and performance, particularly in companies with large boards. However, such combinations did not influence the relationship between independent directors, foreign directors, and the number of meetings in relation to company performance.